(untitled) - Cock, Ian E (Pharmacognosy Communications)
Inflammatory Bowel Disease (IBD) consists of a group of conditions, which each cause inflammation and swelling of tissues of the Gastrointestinal (GI) tract. Of these, Crohn’s disease and ulcerative colitis are the most common together; these conditions afflict millions of people globally, with the most cases occurring in China and the United States of America.1 The symptoms of IBD include abdominal pain and discomfort, diarrhoea, tiredness and lethargy, rectal bleeding and weight loss. The symptoms may manifest in varying levels of severity, IBD can be severe and can even result in life-threatening complications in some individuals. There is a need to develop safe and effective therapies to treat IBD, and recent attention has focussed on traditional therapies and plant-based remedies. Zingiber officinale Roscoe (family Zingiberarceae) has a long history of therapeutic use, including for the treatment of colds and influenza,2 bacterial respiratory infections,3 nausea, arthritis, migraines,4 gastrointestinal infections5 and hypertension.6 Additionally, several preclinical and clinical studies have also investigated the ability of Z. officinale treatment to decrease the severity of IBD symptoms (diarrhoea, abdominal pain).7,8 Despite those studies, the mechanism of action, and the individual components responsible for those effects are still uncertain.